Business Management Training for Millennial Santri: Processed Dragon Fruit Products - Iwan Wicaksono; I Ketut Mahardika; Rayendra Wahyu Bachtiar (Jurnal Inovasi Sains dan Teknologi Untuk Masyarakat, 2025)
Female students of the millennial generation are required to have the ability to recognize and assess opportunities that are relevant to current developments. Business management is a series of activities, practices, and decisions carried out to plan, organize, direct, and control resources and activities in a business or organization to achieve predetermined goals. The purpose of this community service is to train female students on the management of the Millennial Santri Business Studio, especially involving packaging, branding, and sales of processed dragon fruit products as the identity of the Islamic Boarding School's superior products, and expanding offline sales access at bazaars and online on social media. The target of the community service program is 38 female students of Tanwirut Thullab Islamic Boarding School. The method used is the approach of the Millennial Santri Business Studio management training activities used, namely Participatory Rural Appraisal (PRA). The results of the training show that female students have succeeded in implementing safe and attractive packaging steps for processed dragon fruit products. Products are now packaged using containers that are much safer, cleaner, have a more professional visual appearance, and are effectively protected from contamination. In addition, the brand identity "Dapur Santri" as the identity of the superior dragon fruit products of the Islamic Boarding School. Female students expanding their offline sales channels through bazaars and online through social media have significant potential to strengthen business relationships with customers, which can improve profits, marketing and communication strategies, cost efficiency, and effectiveness. The success of this training fostered an entrepreneurial spirit and motivation among the female students. This has resulted in the emergence of a culture of creativity, innovation, and the courage to compete.